The Interaction of ‐ø‐...‐íle with Aspectual Classes in Nyamwezi - Kanijo, Ponsiano Sawaka (My University, 2019)
This study investigates different readings of the construction -ø-...-íle resulting from the interaction with aspectual classes in Nyamwezi, a Bantu language spoken in Tabora, Tanzania. The study is motivated by two observations. Firstly, in previous analyses (Maganga & Schadeberg 1992), it was noted that -ø-...-íle in Nyamwezi selects few verbs, but the patterns governing its distribution were not identified. Secondly, not much has been done on describing the semantics of verbal roots in Nyamwezi (and many other Bantu languages), which appears to be a source of variable temporal interpretations of -ø-...-íle. Based on field data, I show that the first main function of -ø-...-íle is that of stativizer. That is, -ø-...-íle picks out a phase of an event or the entire event (if the event lacks phasic structure) and presents it as a stable, undifferentiated property. -ø-...-íle does so in three different ways, which give three different readings: (i) resultative, when it occurs with achievements, (ii) general present, which occurs with statives and (iii) a progressive-like reading, which occurs with some activity verbs classified as “directed motion verbs” in this study. The discussion of the contrast between these readings is informed by a progressive form -lɪɪ-. Many other activity verbs do not typically occur with -ø- ...-íle. Those that occur with this construction either suggest the change-of-state or condition of the verb’s subject (which has the semantic role of patient; patientive subject) or they are used in a special pragmatic condition where -ø-...-íle is coerced. Coercion of -ø-...-íle expresses a contradiction and/or emphasis, which can be regarded as a second main function of this construction.
Keywords: Bantu language; Tanzania; Nyamwezi